Comparison of CT and MR angiography in evaluation of peripheral arterial disease before endovascular intervention. (May 2016) - Cina, Alessandro; Di Stasi, Carmine; Semeraro, Vittorio; Marano, Riccardo; Savino, Giancarlo; Iezzi, Roberto; Bonomo, Lorenzo
Background: Multidetector computed tomography angiography (MDCTA) and magnetic resonance angiography (MRA) are accurate techniques for selecting patients with peripheral arterial disease for surgical and endovascular treatment. No studies in the literature have directly compared MDCTA and MRA to establish which one should be employed, in patients suitable for both techniques, before endovascular treatment. Purpose: To compare diagnostic performance of MDCTA vs MRA before endovascular intervention. Material and Methods: We prospectively compared MDCTA (64 slices scanner) and MRA (1.5 T scanner; 3D gadolinium-enhanced bolus-chase acquisition plus time resolved acquisition on calves) to stratify 35 patients according to the TASC II score and a runoff severity score. We also evaluated the accuracy of both techniques in each arterial segment. Selective angiography performed during the treatment was the standard of reference. Results: MDCTA and MRA accurately classify disease in the aorto-iliac (accuracy 0.92 for MDCTA and MRA) and femoro-popliteal (MDCTA 0.94, MRA 0.90) segments. MDCTA was more accurate in stratifying disease in the infrapopliteal segments (0.96 vs. 0.9) and in assessing the impairment of runoff arteries (0.92 vs. 0.85) at per-segment analysis. MDCTA showed a higher confidence and a shorter examination time. Conclusion: Our results suggest that MDCTA can be considered as a first-line investigation in patients being candidates for endovascular procedures when clinical history or duplex sonographic evaluation are indicative of severe impairment of the infrapopliteal segment.